Perbandingan Aktivitas Fisik dan Kesehatan Mental pada Siswa Sekolah Dasar di Perkotaan dan Pedesaan - Irna Ningsih; Encep Sudirjo; Anggi Lengkana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze differences in students' physical activity and mental health based on school location, namely rural and urban areas. The study used a quantitative approach with a comparative design. Physical activity data were collected using the Physical Activity Questionnaire for Children (PAQ-C), while mental health was measured using the Strengths and Difficulties Questionnaire (SDQ). Before inferential analysis was conducted, the data were tested for parametric statistical assumptions through normality tests and homogeneity of variance tests. The Shapiro–Wilk test results showed that the data were normally distributed, while the Levene test showed homogeneous data variances. The analysis results using the Independent Samples T-test showed that students in rural areas had higher levels of physical activity than students in urban areas, and this difference was statistically significant. In addition, the t-test results on mental health scores showed a difference between students in urban and rural areas with a significance value of 0.050. Thus, it can be concluded that there are differences in physical activity and mental health of elementary school students based on school location. Rural areas show more supportive conditions than urban areas. This finding highlights the importance of contextual school education and health policies according to environmental characteristics to optimize student well-being. Keywords: Physical activity, Mental Health, Urban, Rural